Vorrei. Corso di lingua italiana di livello elementare 1 e 2 Libro di testo e libro degli esercizi - Baldini, Serena (Manuali - Umanistica, 2019)
This volume, born from the fifteen-year-long experience of teaching in classes of monolingual students from North American Universities, and born from many years of training in the fields of philosophy, linguistics and analysis, aims at meeting the students' essential linguistic needs, while also considering the improvement of the motivational framework as its main educational goal. To this aim, the text's structure is based on communication, and features a wide range of interactive activities in order for the students to be directly in contact with the real context and to be able to use the target language in an authentic way. The manual includes both a Textbook and a Workbook, as well as a section in English with grammar cards and a general glossary. In addition to the activities for the classroom, each unit includes a part dedicated to home exercises and a partial glossary, which the students have to fill in. The text does not offer separated cultural inserts, which are rarely integrated into the didactic programming; on the contrary, it features very short and simple cultural notes.